ITBISA: A Novel and Sustainable Approach for Supporting EFL Learners’ English Proficiency and Digital Literacy - Kurniadi, Didit; Yuliasri, Issy; Wahyuni, Sri; Sakhiyya, Zulfa (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
IT-Based Integrated Skills Approach (ITBISA) represents a pedagogical approach that combines Oxford’s (2001) Integrated Skills Approach (ISA) with digital literacy dimensions outlined by Son (2017), aiming to improve both English proficiency and digital literacy among EFL learners. Developed for TEFL (Teaching English as a Foreign Language) instruction, ITBISA integrates the four essential language skills through the purposeful use of digital tools and platforms. This study investigates the implementation of ITBISA in a university TEFL course by examining perspectives from students and the teacher. The current implementation builds upon previous applications of the approach by incorporating updates to the national curriculum and integrating AI-based technologies to address the evolving challenges of education in the AI era. Data collection involved classroom observations, teacher and student questionnaires, analyzed thematically to identify learning patterns, technological engagement, and pedagogical insights. The findings show that ITBISA creates a learning environment that promotes active participation, critical thinking, and increased digital awareness. Students reported better confidence in using English in academic and digital contexts, while the teacher noted enhanced classroom interaction and student autonomy. ITBISA is shown to be a sustainable and adaptable approach for EFL instruction, offering a forward-looking framework that addresses the dual demands of language mastery and digital competence in today’s AI era.